Media Pembelajaran Sejarah Mataram Kuno Menggunakan Augmented Reality - Nicolas Setiawan; Prya Artha Widjaja (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
The rapid advancement of technology has transformed many aspects of life, including education. Information and Communication Technology (ICT) plays a crucial role in enhancing the quality of learning. One promising technology is Augmented Reality (AR), which offers interactive elements to clarify complex concepts. Based on conversations with a history teacher at SMK Media Informatika, the teaching methods currently used tend to be traditional. Therefore, an AR-based history learning application focusing on the Ancient Mataram Kingdom in Indonesia was developed using the ADDIE Method. This application was created using Unity 3D and the C# programming language. It serves as an interesting addition for students, aiming to increase their interest in learning. The hope is that this research will significantly contribute to the history learning process, providing innovative, effective, and enjoyable media.